Acute dentate nucleus deep brain stimulation modulates corticomotor excitability in chronic stroke survivors - Xin Li; Kenneth B. Baker; Kyle O'Laughlin; Yin-Liang Lin; Kelsey Baker; Robert Chen; Jacqueline Chen; Andre G. Machado; Ela B. Plow (Brain Stimulation)
Background: Deep brain stimulation of the dentate nucleus (DN-DBS) is an emerging therapy to improve upper extremity (UE) motor function after stroke. This study sought to investigate the physiologic mechanisms of acute DN-DBS in chronic stroke survivors enrolled in a phase I trial for DN-DBS. Methods: Twelve chronic stroke participants with moderate-to-severe UE impairment received (acute) single sessions (≥45 min) of active DBS and sham DBS in a sham-controlled, double-blind, cross-over experiment (order randomized). Transcranial magnetic stimulation (TMS) was used to evaluate corticomotor physiology. We also characterized the relationship between acute DBS effects on physiology and baseline clinical and neuroimaging measures, and chronic DBS effects on motor function. Results: Acute active DBS led to an increase in ipsilesional corticomotor excitability evident as a 5.2 % maximal stimulator output (MSO) reduction in active motor threshold (p = 0.017, d = 0.28), but there was no effect of acute sham DBS. Increases in corticomotor excitability observed with acute DBS were associated with higher microstructural integrity of ipsilesional corticospinal tract (r > 0.70, p < 0.017) and dentato-thalamo-cortical pathways (ρ > 0.69, p < 0.022). Gains in corticomotor excitability with acute DBS were associated with higher dexterity gains made with chronic DBS plus rehabilitation (r > 0.65, p < 0.028). Conclusions: Acute DN-DBS leads to heightened ipsilesional corticomotor excitability in moderate-to-severe chronic stroke survivors. Effects of acute DN-DBS on physiology are contingent upon structural preservation of key white matter tracts and associated with motor gains made with chronic DN-DBS. Findings provide mechanistic support of DN-DBS as a potential therapy for post-stroke motor recovery and potential of TMS to monitor responses.